The Concept of A Line In A Pencil Image And Its Types - Mambetkadirova Durdana (Euro Asian Journal Publishing, 2024)
this article gives information about the concept of a line in a pencil image and its types, there are also works of Uzbek national artists
Keywords: Line; companion; sculpture; installation; land art